SOSIALISASI PENDAMPINGAN ORANGTUA DALAM PEMAHAMAN POLA HIDUP SEHAT DI ERA COVID – 19 - insenalia Hutagalung; Asima Rohana Sinaga; Apriani Sijabat (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
In early 2020, the world was shocked by an outbreak of a new disease that started in Wuhan, Hubei Province, which then spread rapidly to more than 190 countries and territories. This outbreak was named coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has had a broad social and economic impact as well as educationDuring this time of COVID-19, it has had a major influence on human life, both in terms of thinking and even in people's lifestyles, which has made this very important, especially in health. A healthy lifestyle plays an important role in the Covid-19 Pandemic. For this reason, there is a need for socialization in providing an understanding of Healthy Lifestyles to be prioritized in the community so that this is also one way to reduce the spread of the epidemic which is preventive in nature. The method used is the method of socialization held in the village of Siantar Estate. As a result, the community increasingly understands the Healthy Lifestyle with Nutritious Food and maintains cleanliness.